KERJASAMA EKONOMI DIGITAL INDONESIA DAN SINGAPURA DALAM TEKNOLOGI FINANSIAL TAHUN 2017-2020 - Dimas Bhayu Akoso, (2024)
The fourth industrial revolution has led to an increased use of technology worldwide, including in the economic sector. One such sector is financial technology, a new industry that has proven to be excellent for digital economic activities. To support its growth, the Indonesian government is collaborating with the Singaporean government. The cooperation between Indonesia and Singapore will allow financial technology companies to enter both countries without barriers and exchange information on regulatory development and market conditions. The aim of the cooperation is also to improve Indonesia's financial literacy index. However, the implementation of this aim has not yet resulted in an increase in the index. This research aims to investigate the implementation of financial technology cooperation between Indonesia and Singapore from 2017 to 2020. To obtain accurate research results, this study employs the theory of bilateral cooperation and the concept of financial technology. A qualitative method with a descriptive analysis research approach is also utilized. The study's results indicate that cooperation is beneficial for the development of regulatory sandboxes, which are being created and implemented in Indonesia. These sandboxes will aid in the growth of the financial technology industry and provide various benefits, such as testing digital financial innovation products, exchanging information to incorporate financial technology into the curriculum, and facilitating the entry of financial technology companies from both countries into Indonesia and Singapore.